Grain yield improvement in high-quality rice varieties released in southern China from 2007 to 2017 - Wang, Haixia; Xiong, Ruoyu; Zhou, Yanzhi; Tan, Xueming; Pan, Xiaohua; Zeng, Yongjun; Huang, Shan; Shang, Qingyin; Xie, Xiaobing; Zhang, Jun; Zeng, Yanhua (Frontiers in Sustainable Food Systems, 2022)
High-quality rice varieties in recent years are widely cultivated for production in southern China. However, the yield performances changes of different high-quality rice varieties types released are still unclear. In this study, these different type varieties released including hybrid or inbred rice and japonica or indica rice were compared for the grain yield performances changes and current status, presenting breeding target of high-quality rice. Results showed that from 2007 to 2017, the grain yield and yield traits including spikelets per panicle and seed-set of high-quality indica rice varieties significantly increased, while the productive tillers decreased only in indica inbred rice; and the grain yield of high-quality japonica rice also significantly increased, whereas japonica hybrid rice had the increasing spikelets per panicle and the decreasing productive tillers. Compared with inbred rice, hybrid rice significantly increased grain yield due to higher spikelets, rather than lower productive tillers and seed-set. Meanwhile, japonica rice had higher grain yield than indica rice, attributed to seed-set and optimized structure between productive tillers and spikelets. In addition, the grain yield variation coefficient of japonica rice decreased, whereas increased in indica rice over time, and those of productive tillers and seed-set tended to be stable. Zhejiang Province had the higher grain yield owing to the increasing spikelets per panicle and seed-set over time among the six provinces. Our results suggested that based on the increasing yield potential of high-quality rice varieties in the past 11 years, future high-quality rice breeding should be emphasized for improving the productive tillers and seed-set for hybrid rice, and the spikelets for inbred rice, especially grain weight for indica inbred rice.